Situating Children of Migrants across Borders and Origins: A Methodological Overview - Bolzman, Claudio; Bernardi, Laura; Le Goff, Jean-Marie (Life Course Research and Social Policies, 2017)
intergenerational relations; transfer behaviour; migration; multicultural; religious identity; research methods; second generation